New spatial analyses of Australian wildfires highlight the need for new fire, resource, and conservation policies - Lindenmayer, David B.; Taylor, Chris (Proceedings of the National Academy of Sciences - PNAS, 2020)
Extensive and recurrent severe wildfires present complex challenges for policy makers. This is highlighted by extensive wildfires around the globe, ranging from western North America and Europe to the Amazon and Arctic, and, most recently, the 2019–2020 fires in eastern Australia. In many jurisdictions, discussions after significant losses of life, property, and vegetation are sometimes conducted in the absence of nuanced debates about key aspects of climate, land, and resource management policy. Improved insights that have significant implications for policies and management can be derived from spatial and temporal analyses of fires. Here, we demonstrate the importance of such analyses using a case study of large-scale, recurrent severe wildfires over the past two decades in the Australian state of Victoria. We overlaid the location of current and past fires with ecosystem types, land use, and conservation values. Our analyses revealed 1) the large spatial extent of current fires, 2) the extensive and frequent reburning of recently and previously fire-damaged areas, 3) the magnitude of resource loss for industries such as timber and pulplog production, and 4) major impacts on high conservation value areas and biodiversity. These analyses contain evidence to support policy reforms that alter the mode of forest management, target the protection of key natural assets including unburnt areas, manage repeatedly damaged and potentially collapsed ecosystems, and expand the conservation estate. Our mapping approach should have applicability to other environments subject to large-scale fires, although the particular details of policy reforms would be jurisdiction, ecosystem, and context specific.